2012
DOI: 10.1186/1471-2458-12-138
|View full text |Cite
|
Sign up to set email alerts
|

Does social capital travel? Influences on the life satisfaction of young people living in England and Spain

Abstract: BackgroundThis study used a social capital framework to examine the relationship between a set of potential protective ('health assets') factors and the wellbeing of 15 year adolescents living in Spain and England. The overall purpose of the study was to compare the consistency of these relationships between countries and to investigate their respective relative importance.MethodsData were drawn from the 2002, English and Spanish components of the WHO Health Behaviour in School-Aged Children (HBSC) survey A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 48 publications
1
49
1
1
Order By: Relevance
“…Studies have demonstrated that higher levels of family social capital are associated with better mental health in children (Almedom, 2005;Dorsey and Forehand, 2003;Morrow, 1999;Wu et al, 2010a). For example, Morgan et al (2012) analyzed data from 3591 adolescents in England and Spain, finding that two measures of family social capital, family autonomy and control and family sense of belonging, were significantly related to adolescents' life satisfaction in both countries. Using data from the National Longitudinal Survey of Youth (NLSY79) in the United States, Dufur et al's (2008) study on 1833 children aged 5e14 years also demonstrated that family social capital, assessed by parents' knowledge of the child's activities and potential time spent with children, was strongly predictive of better child social adjustment.…”
Section: Social Capital and Child Mental Healthmentioning
confidence: 95%
“…Studies have demonstrated that higher levels of family social capital are associated with better mental health in children (Almedom, 2005;Dorsey and Forehand, 2003;Morrow, 1999;Wu et al, 2010a). For example, Morgan et al (2012) analyzed data from 3591 adolescents in England and Spain, finding that two measures of family social capital, family autonomy and control and family sense of belonging, were significantly related to adolescents' life satisfaction in both countries. Using data from the National Longitudinal Survey of Youth (NLSY79) in the United States, Dufur et al's (2008) study on 1833 children aged 5e14 years also demonstrated that family social capital, assessed by parents' knowledge of the child's activities and potential time spent with children, was strongly predictive of better child social adjustment.…”
Section: Social Capital and Child Mental Healthmentioning
confidence: 95%
“…This also suggests the multi-contextual nature of social capital, identifying the different social networks that contribute to securing adolescents’ sense of belonging. Other studies suggest that, by assessing the relative importance of adolescents’ social capital within the family, school, and neighborhood contexts, a better understanding of the impact of these contexts on adolescents’ self-rated health will be obtained [23]. …”
Section: Introductionmentioning
confidence: 99%
“…LS as well as SRH are seen to be important components of broader strategies oriented to improve health and overall quality of life for children and young people (29).…”
Section: Introductionmentioning
confidence: 99%